Please help me it’s simple but I just have forgotten
![Please help me its simple but I just have forgotten class=](https://us-static.z-dn.net/files/d82/b3e8895e826902924e089a4e4e04a118.png)
9514 1404 393
Answer:
y = -3x
Step-by-step explanation:
Your solution will be in the form ...
y = (something)
In order to get the y-term by itself, you need to add the opposite of everything else*:
3x +y +(-3x) = 0 +(-3x)
y = -3x . . . . . simplify
_____
* Anything you do to one side of the equation must also be done to the other side. Here, we added -3x to both sides.